Trends in the Utilization of Life-Sustaining Procedures and Palliative Care Consultation Among Dying Patients With Advanced Chronic Pancreas Illnesses in US Hospitals: 2005 to 2014. Issue 4 (October 2019) - Liu, Xibei; Shen, Jay J.; Kim, Pearl; Kim, Sun Jung; Ukken, Johnson; Choi, Younseon; Hwang, In Choel; Lee, Jae-Hoon; Chun, Sung-Youn; Hwang, Jinwook; Choi, Haneul; Yeom, Hyeyoung; et al.
Aim: Pancreas cancer continues to carry a poor prognosis. Hospitalized patients with advanced chronic pancreatic illnesses increasingly receive palliative care due to its perceived clinical benefits. Meanwhile, a growing proportion of elderly patients are reportedly receiving life-sustaining procedures. Temporal trends in the utilization of life-sustaining procedures and palliative care consultation among dying patients with advanced chronic pancreatic illnesses in US hospitals were examined. Methods and Materials: A serial, cross-sectional analysis was carried out using the National Inpatient Sample Database. Decedents 18 years and older with a principal diagnosis of pancreas cancer or other advanced chronic pancreatic illnesses from 2005 through 2014. The compound annual growth rates (CAGRs) and Cochrane-Armitage correction of χ 2 statistic were used. The receipt of life-sustaining systemic procedures, intra-abdominal local procedures and surgeries, and palliative care consultation were examined. Multilevel multivariate logistic regressions were performed to examine the association of various procedures with the utilization of palliative care consultation. Results: Among 77 394 183 hospitalizations, 29 515 patients were examined. The CAGRs of systemic procedures, intra-abdominal procedures, surgeries, and palliative care were −4.19% ( P = .008), 2.17%, −1.40%, and 14.03% ( P < .001), respectively. The receipt of systemic procedures (odds ratio [OR] = 2.40, 95% confidence interval [CI], 2.08-2.74), local intra-abdominal procedures (OR = 1.46, 95% CI, 1.27-1.70), and surgeries (OR = 2.51, 95% CI, 2.07-3.05) was associated with palliative care consultation ( P s < .001). Conclusions: Among adults with pancreatic cancer or other advanced chronic pancreatic illnesses in the US hospitals from 2005 to 2014, the utilization of life-sustaining systemic procedures decreased while the prevalence of palliative care consultation increased.